2011
DOI: 10.1007/978-3-642-25821-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Leader Election for Replicated Services Using Application Scores

Abstract: Abstract. Replicated services often rely on a leader to order client requests and broadcast state updates. In this work, we present POLE, a leader election algorithm that select leaders using application-specific scores. This flexibility given to the application enables the algorithm to tailor leader election according to metrics that are relevant in practical settings and that have been overlooked by existing approaches. Recovery time and request latency are examples of such metrics. To evaluate POLE, we use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Becker et al [3] have shown how the leader election influences the response time for cases in which the request distribution is skewed. In our example, if all requests are issued at replica s 1 , replica s 1 is a better leader than, for instance, replica s 2 .…”
Section: A Motivating Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Becker et al [3] have shown how the leader election influences the response time for cases in which the request distribution is skewed. In our example, if all requests are issued at replica s 1 , replica s 1 is a better leader than, for instance, replica s 2 .…”
Section: A Motivating Examplesmentioning
confidence: 99%
“…Electing a good leader for replication in WAN has been studied by Becker et al [3]. In their work, they propose a bullying [8] leader election configurable with user-defined scores.…”
Section: G Optimizing For Connection Countmentioning
confidence: 99%
“…Other research proposes a model based on watchers in ZooKeeper and define a watch as a trigger that causes an event to be dispatched to the client whenever the watched resource changes its state. Due to the fact that the processes are asynchronous and as a consequence, the network latency gives rise to multiple possible orderings of network messages; so the model was improved in order to enable consistency [2,3]. Another proposal for a leader election algorithm for replicated services that are based on a leader, updates propagation and client request was POLE (Performance-Oriented Leader Election) [5], the algorithm selects the leader depending on an application specificity.…”
Section: Why Another Algorithm?mentioning
confidence: 99%